مظاهر التفكك العائلي لجنوح الإناث - العيساوي، هادي صالح; علي، صبا حسن عبد (جامعة بغداد - كلية التربية للبنات, 2016)
العائلة مؤسسة اجتماعية مهمة في المجتمع، فإذا استقامت وصلحت صلح المجتمع وغالبا ما تؤدي تلك المؤسسة دورها الإيجابي في التنشئة الاجتماعية، إلا أن هناك مجموعة من العوامل المعتلة تصيب النظام العائلي فتفقده دوره المؤثر والفاعل في المجتمع ويقف في مقدمة تلك العوامل التفكك العائلي سواء كان ناتجا عن وفاة أحد الأبوين أو كلاهما أو الطلاق أو الانفصال، أو سواء ناتجا عن الضعف العائلي والممارسات السلوكية العائلية السيئة. تكتسب هذه الدراسة أهمية كبيرة وذلك لندرة الدراسات التي تعالج مشكلة جنوح الإناث، ولا يخفى بأن الوقوف على حقيقة دور التفكك العائلي في احداث تلك المشكلة سيساعد ولدرجة كبيرة في وضع التوصيات والمقترحات التي تهد من خطورة هذه المشكلة، وسيساهم بالتالي في تقوية دعائم الكيان العائلي ليأخذ دوره الفاعل في التنشئة الاجتماعية السليمة من خلال العمل على معالجة مشكلات التفكك العائلي وبما يحد من أثارها المدمرة على الأبناء وما ينعكس جراء ذلك سلبا على البناء الاجتماعي، ويتضمن البحث ستة مباحث وقد توصلنا إلى نتائج من أهمها: 1. أسهم التفكك العائلي الناتج بوفاة أحد الوالدين أو كلاهما في جنوح الأحداث الإناث الجانحات. 2. أظهرت الحالات التي واجهت العاملين وكان فيها أحد الوالدين مطلقان وتزوج الأخر كان سببا لجنوح الإناث. 3. وجد أن انفصال الوالدين وزواج الأب مرة ثانية كان سببا لجنوح الإناث. ومن التوصيات التي تقترحه الباحثة كالآتى:- 1. العمل على رفع المستوى المعاشي للعوائل لإزالة حالة الفقر التي تقود إلى تشغيل البنات بسن مبكر وتساعد في تسربهن الدراسي وبالتالي في جنوحهن، وهذه من مهمة وزارة العمل والشؤون الاجتماعية. 2. بما أن اغلب الجانحات يعيشن في مناطق فقيرة، عليه فالضرورة نستوجب العمل على رفع مستوى الحياة في هذه المناطق وخاصة في مجال الخدمات، ويمكن أن تسهم في ذلك وزارة الصحة والبلديات والشباب والرياضة من خلال توفير الخدمات الصحية المتمثلة بالماء والمجاري وبناء مستوصف صحي وملاعب رياضية.
Family social institution mission in the community, if and repaired Magistrate society and often lead that institution a positive role in the socialization, but a variety of factors ailing infect system family Vtfkdh role effective and influential in society and stands at the forefront of those factors disintegration family, whether caused by the death of one or both parents, divorce or separation, or whether the result of domestic weakness and poor family behavioral practices. And gaining the study of great importance and that the scarcity of studies that address the problem of delinquency female, is no secret that stand on the fact the role of disintegration family in the events of that problem will help and a large degree in the development of recommendations and proposals that limit the severity of the problem, and will therefore strengthen the pillars of the entity's family take turns actor in the proper socialization through work to address the problems of family disintegration and including limits of its devastating effects on children and the result is reflected negatively on the social construction, and research includes six sections have reached an outcome of the most important 1- Shares family disintegration caused the death of one or both parents in juvenile delinquency delinquent females. 2- Cases showed that workers faced was where one of the parents are divorced and married the other was the cause of female delinquency. 3- Found that the separation of parents and father again marriage was the cause of female delinquency. Among the recommendations proposed by the researcher as follows: 1. Work to raise the standard of living of the families to remove poverty, which leads to run an early age girls and help in the school dropout and thus in Jnohan, this task of the Ministry of Labour and Social Affairs. 2. Since most delinquent Aaishn in poor areas, it Valdharorh Nstojb work to raise the quality of life in these areas, especially in the area of services, and can contribute to the Ministry of Health and municipalities, Youth and Sports through the provision of health services of water, sewage and building health clinic and sports fields.
Keywords: التنشئة الاجتماعية -- التفكك الأسري -- الممارسات السلوكية -- المناطق الفقيرة -- تشغيل البنات